Effectiveness of an Electronic Automated Antibiotic Time Out Alert in the Setting of Gram-Negative Bacteremia - Sana M. Mohayya; Navaneeth Narayanan; Daniel Cimilluca; Alexander Malanowski; Parth Vaidya; Tanaya Bhowmick (MDPI AG, 2021)
To minimize complications associated with over-utilization of antibiotics, many antimicrobial stewardship programs have incorporated an antibiotic time out (ATO); however, limited data are available to support its effectiveness. This was a single-center retrospective cohort study assessing the impact of the automated electronic ATO in the setting of Gram-negative bacteremia. The primary outcome was the proportion of patients who received a modification of therapy within 24 h of final culture results. Secondary outcomes included modification at any point in therapy, time to modification of therapy, time to de-escalation, and days of therapy of broad-spectrum antibiotics. There was a total of 222 patients who met inclusion criteria, 97 patients pre-ATO and 125 patients post-ATO. The primary outcome of modification of therapy within 24 h of final culture results was not significantly different (24% vs. 30%, p = 0.33). The secondary outcome of modification of therapy at any point in therapy was not significantly different between the two groups (65% vs. 67%, p = 0.73). All other secondary outcomes were not significantly different. The ATO alert was not associated with a higher rate of antibiotic modification within 24 h of culture results in patients with GNB. Further efforts are needed to optimize the ATO strategy and antibiotic prescribing practices.